Pengaruh Kecerdasan Intelektual dan Kecerdasan Emosional dalam Perspektif Neurosains di Dunia Pendidikan - Permata, Indah; Asbari, Masduki; Ariansyah; Aprilia, Merita (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to determine the importance of intellectual intelligence and the influence of emotional intelligence in the world of education. This study report uses a descriptive qualitative lecture method by listening and taking notes because the source of the information was obtained from one of Gita Wirjawan's YouTube channels, namely about